Detection of IgM antibrucella antibody in the absence of IgGs: a challenge for the clinical interpretation of brucella serology. - Julián Solís García Del Pozo; Santiago Lorente Ortuño; Elena Navarro; Javier Solera (PLoS Neglected Tropical Diseases)
The use of enzyme-linked immunosorbent assay (ELISA) for the detection of IgG and IgM antibodies antibrucella has become widespread in the diagnosis of human brucellosis. IgM anti-Brucella antibodies are indicative of acute infection. Between 2009-2013, 5307 patients were evaluated for serologic diagnosis at the Microbiology Laboratory of the Albacete General Hospital. A ELISA IgM-positive, IgG-negative anti-Brucella antibody serology pattern was detected in 17 of those patients. Epidemiology data, symptoms, laboratory data, treatment and outcome from these patients were reviewed. Sixteen patients presented with musculoskeletal pain, fatigue and/or fever and 1 was asymptomatic. Five patients received treatment with doxycycline combined with rifampin, gentamycin or streptomycin during 6-12 weeks, with no improvement. None of the 17 patients were finally diagnosed with brucellosis. Our results indicate that anti-Brucella IgM positive serology, per se, is not enough to diagnose acute brucellosis and other methods should be used for confirmation. Brucella serology data should be interpreted taking into account the patient's clinical history and epidemiological context.